Anatomy of explosives spontaneous combustion accidents in the Chinese underground coal mine: Causes and prevention. Issue 3 (16th March 2016) - Wang, Jianhao; Zhang, Jiangshi; Zhu, Kai; Zhou, Lin
Abstract : Explosives spontaneous combustion accidents in underground coal mines have not been taken seriously in China despite serious casualties and property losses. In order to avoid disasters of this sort, anatomy on eight accidents were performed, mainly involving the process of the occurrence and development, characteristics of casualties, causes and prevention. Improper storage and use of shoddy explosives were the primary reasons for these accidents. Toxic gases and smoke were generated in the explosives' smoldering or burning, so the poisoning and suffocation were the main types of casualties. Besides, unsafe acts of different staff, which resulted in the occurrence of accidental events and the expansion of casualties (i.e., affecting the evacuation and rescue), were analyzed emphatically, and almost all of them were violations. The senior manager and middle manager were the main producers of unsafe acts, which can provide the guidance for employees' targeted training and supervision. Overall, eliminating unsafe acts is an effective way to prevent this kind of accidents, and casualties can be reduced or even avoided through the proper evacuation and rescue. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 221–227, 2016